Outcomes of completion lobectomy long after segmentectomy - Yuki Takahashi; Masahiro Miyajima; Makoto Tada; Ryunosuke Maki; Taijiro Mishina; Atsushi Watanabe (Journal of Cardiothoracic Surgery, 2019)
Abstract Background Completion lobectomy long after segmentectomy in the same lobe is extremely difficult because of severe adhesions around hilar structures, especially in cases involving video-assisted thoracoscopic surgery (VATS) completion lobectomy. We report and compare the surgical outcomes of patients who underwent VATS or thoracotomy completion lobectomy long after radical segmentectomy for lung cancer. Methods We retrospectively evaluated the surgical outcomes of completion lobectomies performed at our institute long after radical segmentectomies for lung cancer in the same lobe. The efficacy and safety of VATS completion lobectomy was compared to that of thoracotomy completion lobectomy. Results Ten of 228 patients who underwent radical segmentectomy for lung cancer between 2009 and 2018 underwent completion lobectomy at least a month after segmentectomy; five patients underwent VATS completion lobectomy. None of the patients underwent VATS left upper completion lobectomy, and conversion to thoracotomy was required in one patient. There were no significant differences between VATS and thoracotomy completion lobectomies in the median operative times (VATS 295 min, thoracotomy 339 min, p = 0.55), intraoperative blood loss volumes (VATS 350 mL, thoracotomy 500 mL, p = 0.84), intervals between initial segmentectomy and completion lobectomy (VATS 40 months, thoracotomy 48 months, p = 0.55), and number of patients with pulmonary artery injury (VATS 1, thoracotomy 2, p = 0.49). There was no operation-related mortality. Conclusions VATS completion lobectomy long after segmentectomy for lung cancer could be performed without fatal complications unless severe adhesions are observed around each main pulmonary artery.